Penentuan Critical Parts Alat Bantu Pemeras Santan Menggunakan Quality Function Deployment Fase Kedua - Hadi, Yuswono; Dahlan, Ahmad Faishal (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
Some previous studies used QFD first phase method to obtain customer satisfaction of coconut milk squeezer machines, as follows: accelerates extortion process, reduces fatigue, easy to use, optimizes the output, strong construction, rustproof materials, compact design, easy to move, and hygienic. Study developing of the squeezer machine of coconut milk is required to deploy customer satisfaction into two parts including specifications and critical parts by using QFD second phase. There are 15 part specifications that obtained by discussing and interviewing with the experts. Then, 4 part specifications such as motor, pressing mechanism, production step, pressing strength, and volume of the cylinder were selected as main part to be used for QFD second phase. While there were 10 critical parts was derived from selected part specification such as pressure strength, hydraulic system, ON/OFF push button, cylinder clamps, the power and voltage that used for the machine,Â the piston holder material, and its diameter.